2014
DOI: 10.2174/1389203715666140327111139
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Photophysical Properties of the Peridinin-Chlorophyll-a-Protein

Abstract: Peridinin-Chlorophyll-a-Proteins (PCPs) are water-soluble light harvesting complexes from dinoflagellates. They have unique light-harvesting and energy transfer properties which have been studied in details in the last 15 years. This review aims to give an overview on all the main aspects of PCPs photophysics, with an emphasis on some aspects which have not been reviewed in details so far, such as vibrational spectroscopy studies, theoretical calculations, and magnetic resonance studies. A paragraph on the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 136 publications
(230 reference statements)
0
38
0
Order By: Relevance
“…These pigments seemed to be pure enough to use the apex as a reference (Retention time and λ max ) in Table 2 . These kinds of spectra are not very common but provide a consistent signal [ 51 ]. Carotenoids are involved in chlorophyll photoprotection.…”
Section: Discussionmentioning
confidence: 99%
“…These pigments seemed to be pure enough to use the apex as a reference (Retention time and λ max ) in Table 2 . These kinds of spectra are not very common but provide a consistent signal [ 51 ]. Carotenoids are involved in chlorophyll photoprotection.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the early publication of PCP high-resolution X-ray structure 1 revealed that this water-soluble protein has a pseudo-two-fold symmetry and binds eight peridinins (Pers) clustered around two Chl molecules. The detailed structural information, together with the remarkable efficiency for excitation energy transfer (EET) from Car donors to Chl acceptors (~90%) 2 5 , have inspired intense research among the biophysical community 6 12 . While the properties of Cars as leading actors in photoprotection 13 and non-photochemical quenching 14 have been the object of several in-depth investigations in the last decades 15 17 , the mechanistic and dynamic details of the excitation energy flow from Cars to Chls are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The light-harvesting peridinin-chlorophyll-protein (PCP) from the dinoflagellate Amphidinium carterae [20] in its native form is a trimer, where each of the monomers comprises eight peridinin molecules and two Chls a embedded in a protein scaffold [20,[32][33][34]. As shown in Figure 2b, the absorption spectrum of PCP (black) features a band in the range from~400 to 550 nm due to peridinins, while Chl a molecules absorb light in the Soret band (with a maximum around 440 nm) and in the Q y region from 600 to 670 nm.…”
Section: Photosynthetic Complexesmentioning
confidence: 99%